2017
DOI: 10.1186/s13567-017-0468-8
|View full text |Cite
|
Sign up to set email alerts
|

Which phenotypic traits of resistance should be improved in cattle to control paratuberculosis dynamics in a dairy herd: a modelling approach

Abstract: Paratuberculosis is a worldwide disease causing production losses in dairy cattle herds. Variability of cattle response to exposure to Mycobacterium avium subsp. paratuberculosis (Map) has been highlighted. Such individual variability could influence Map spread at larger scale. Cattle resistance to paratuberculosis has been shown to be heritable, suggesting genetic selection could enhance disease control. Our objective was to identify which phenotypic traits characterising the individual course of infection in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Domestic ruminants (cattle, sheep and goat) are the commonly affected animals with MAP [ 29 ]. Susceptibility to MAP infection decreases with age; thus age together with the infecting dose and some other factors contribute to limiting the spread of MAP [ 30 ]. It is now known that not all animals exposed to MAP develop JD and some appear to clear the infection spontaneously.…”
Section: Susceptibility To Infection With Mapmentioning
confidence: 99%
“…Domestic ruminants (cattle, sheep and goat) are the commonly affected animals with MAP [ 29 ]. Susceptibility to MAP infection decreases with age; thus age together with the infecting dose and some other factors contribute to limiting the spread of MAP [ 30 ]. It is now known that not all animals exposed to MAP develop JD and some appear to clear the infection spontaneously.…”
Section: Susceptibility To Infection With Mapmentioning
confidence: 99%
“…However, the low dose used in this study, 5 x 10 7 given over two consecutive days, was higher than the minimal doses of 1.5 x 10 6 used in other studies, (Sweeney et al, 2006). Nevertheless, this observation could have considerable consequences for control programmes: a recent French modelling study reported that the rate of decay in susceptibility with age had a dramatic effect on within-herd transmission (Ben Romdhane et al, 2017).…”
Section: Infection Susceptibilitymentioning
confidence: 53%
“…This work demonstrated that the association between shedding levels and infectiousness is not linear; in fact, a 1000-fold increase in bacterial shedding results in only a 2-3 fold increase in infectiousness (Slater et al, 2016). However, other research groups have found that the level of MAP shedding from individual animals is one of the most important control phenotypic traits that can impact on the spread of infection (Ben Romdhane et al, 2017). In addition, field and research observations do support clusters of infection occurring in time and space (Zare et al, 2013).…”
Section: Map-shedding and Exposurementioning
confidence: 81%